A Single, Acute Astragaloside IV Therapy Protects Cardiomyocyte Through Attenuating Superoxide Anion-Mediated Accumulation of Autophagosomes in Myocardial Ischemia-Reperfusion Injury - Huang, Kai-yu; Yu, Yong-wei; Liu, Shuai; Zhou, Ying-ying; Wang, Jin-sheng; Peng, Yang-pei; Ji, Kang-ting; Xue, Yang-jing (Frontiers in Pharmacology, 2021)
Myocardial ischemia-reperfusion (I/R) injury, characterized by myocardial cell death (e.g., apoptosis) and generation of reactive oxygen species (ROS) such as superoxide (O2·−) and hydrogen peroxide (H2O2), is a serious threat to human health and property. Saponin astragaloside IV (ASIV), extracted from Chinese herbal medicine astragalus, is effective in resolving multiple pathological issues including myocardial I/R injury. Recent studies have shown that autophagy is regulated by ROS and plays an important role in myocardial I/R injury. However, regulation of autophagy by ASIV during myocardial I/R injury and the role of specific ROS involved in the process have been rarely reported. In the present study, we found that SOD2 was downregulated and O2·− was upregulated in H2O2-induced H9C2 cardiac myocyte injury in vitro and myocardial I/R injury in vivo, while such alterations were reversed by ASIV. ASIV possessed the ability to alleviate myocardial I/R injury via attenuating I/R-caused autophagosome accumulation. Upregulate of O2·− by 2-methoxyestradiol (2-ME) reversed the effect of ASIV-mediated autophagy regulation, which suggested that O2·− was vital in this process. In conclusion, our results contribute to understanding the mechanism of ASIV-induced cardioprotective effect.